An introduction to granular flow - Rao, K. Kesava (Cambridge University Press, 2008)
The flow of granular materials such as sand, snow, coal, and catalyst particles is common occurrence in natural and industrial settings. The mechanics of these materials is not well understood. They are important since a large fraction of the materials handled and processed in the chemical, metallurgical, pharmaceutical, and food processing industries are granular in nature. This book describes the theories for granular flow based mainly on continuum models although alternative discrete models are also discussed briefly. The level is appropriate for advanced undergraduates or beginning graduate students. The goal is to inform the reader about observed phenomena, some available models, and their shortcomings and to visit some issues that remain unresolved. There is a selection of problems at the end of the chapters to encourage exploration, and extensive references are provided.